Pregnancy Exercises for Pregnant Women at Home During the Covid-19 Pandemic in the Work Area of the Telaga Biru Health Center, Gorontalo Regency - Harismayanti Harismayanti; Ani Retni; Irma Suryanti Dunggio; Moh. Rivaldo Adam; Aninda J. Noiyo (Journal of Universal Community Empowerment Provision, 2021)
Pregnancy exercise is a fitness program intended for pregnant women. Therefore, pregnancy exercise has the principles of special movements that are adapted to the condition of pregnant women. The exercises in pregnancy gymnastics are specially designed to make pregnant women healthy and fit, reduce complaints that arise during pregnancy, and prepare physically and psychologically for mothers to face childbirth. The purpose of community service is to increase knowledge of pregnant women about Pregnancy Exercises during pregnancy in the Telaga Biru Health Center Work Area in order to increase health care during pregnancy during the Covid-19 pandemic. The method used is education using Power Points, Leaflets, and demonstrations about Pregnancy Exercises for Pregnant Women during the Covid-19 Pandemic. . The results of this activity achieved good results because as many as 10 pregnant women were willing to take part in counseling and were willing to apply Maternity Gymnastics at home during the Covid-19 pandemic. The conclusion of this community service is that counseling can increase participants' knowledge and can understand and apply counseling materials in everyday life